Biosensors for Environmental Monitoring and Biomedical Applications - Štofik, Marcel (Jihočeská univerzita, 2012)
Study of biosensors has become an essential part of research in biotechnology. Biosensors as fast, portable, highly sensitive, and low-cost bioanalytical detection devices have been utilized in many fields of human activity. The first part of the presented work focuses on electrochemical biosensors for rapid environmental screening of herbicides as water pollutants. A sol-gel immobilization method for a photosystem II (PSII) complex is studied in order to enhance the sensitivity and the signal strength and stability of a PSII-based biosensor. Computer simulations of a PSII biosensor are employed with the aim to find out how the immobilization membrane properties influence the biosensor parameters. Newly developed immobilization by a thin-layer membrane based on the results of computer simulations and revised measurement protocols are presented. The second part of the work is devoted to synthesis and electrochemical detection of newly developed metal labels for electrochemical immunosensors. The synthesis of dendrimer-encapsulated silver nanoparticles and biorecognition properties of biotin-nanocomposite conjugates are discussed. For detection of synthesized labels, a microfluidic detector was manufactured and tested and different approaches to packing of a microfluidic chip employing polydimethylsiloxane (PDMS) were investigated. Newly designed microstructures for a microfluidic separator of magnetic beads (MBs) were studied by computer simulations. The separator was made and trapping of MBs for the further employment in MBs-based immunoassays are presented
Biosensors for Environmental Monitoring and Biomedical Applications
Keywords: biosensors; photosystem II; PSII-biosensor; sol-gel immobilization; diglyceryl silane; herbicide; diuron; EC50; LOD; computer simulation; PAMAM-OH dendrimer; dendrimer nanocomposite; silver enhancement; stripping analysis; immunosensors; metalloimmunoassay; biotinylation; microfluidics; microfabrication; electrochemical cell; microelectrodes; holder; magnetic beads; magnetic separation; planar micro-electromagnet; biosensors; photosystem II; PSII-biosensor; sol-gel immobilization; diglyceryl silane; herbicide; diuron; EC50; LOD; computer simulation; PAMAM-OH dendrimer; dendrimer nanocomposite; silver enhancement; stripping analysis; immunosensors; metalloimmunoassay; biotinylation; microfluidics; microfabrication; electrochemical cell; microelectrodes; holder; magnetic beads; magnetic separation; planar micro-electromagnet